Analisis Penghindaran Pajak: Peran Struktur Kepemilikan - Saputra, Ahmad Reza; Tarmidi, Deden (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the effect of institutional ownership, foreign ownership, and concentrated ownership on tax avoidance. The research objects are non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Samples were selected using purposive sampling, resulting in 112 observations from 28 companies. A quantitative approach was employed with multiple linear regression analysis, processed using EViews software. The findings indicate that institutional ownership has a significant positive effect on tax avoidance, while foreign ownership has a significant negative effect. Meanwhile, concentrated ownership has no significant effect. These results suggest that ownership structure characteristics influence corporate decisions in designing tax efficiency strategies. This study provides important implications for regulators and investors to consider the composition of share ownership in promoting fiscal compliance and strengthening corporate governance practices.